Stander Use for an Adolescent with Cerebral Palsy at GMFCS Level with Hip and Knee Contractures. Issue 6 (1st November 2020) - Capati, Vicente; Covert, Stephanie Yu; Paleg, Ginny
ABSTRACT: Aims : Adolescents with cerebral palsy (CP) report high rates of pain and contractures. Standing may positively affect these outcomes, yet there are no published studies on how to accommodate contractures or when a stander is no longer beneficial. This is the first study that answers the question: Can an adolescent with CP and 40-degree knee and/or hip flexion contractures benefit from a standing program, after being non-weight bearing for many years? Methods : A 16-year-old male with spastic tetraplegic CP, Gross Motor Function Classification System (GMFCS) level V, used a stander with a "knee and hip contracture system." Knee and hip extension, as well as upright inclination, were increased weekly. Knee and hip passive range of motion (PROM) measurements, pain scale, and a parent survey were completed at baseline, 7 and 15 months. Results : After 15 months of stander use, both hips and left knee PROM improved. The subject's activity and participation increased, while pain, suppository use, and time spent on bowel care decreased. Conclusion : An adolescent with 40-degree knee and hip flexion contractures may be positioned well in a stander with a specialized contracture system. PROM, bowel function, pain, activity, and participation may improve for some adolescents at GMFCS level V, through use of a stander.